Theory-based digital intervention to promote weight loss and weight loss maintenance (Choosing Health): protocol for a randomised controlled trial - Felix Naughton; Martin S Hagger; Suzanne Robinson; Dominika Kwasnicka; Aleksandra Luszczynska; Eleanor Quested; Sherry L Pagoto; Peter Verboon; Anna Januszewicz; Paulina Idziak; Iga Palacz-Poborczyk (BMJ Open)
Introduction Digital behavioural weight loss interventions have the potential to improve public health; however, these interventions are often not adequately tailored to the needs of the participants. This is the protocol for a trial that aims to determine the effectiveness and cost-effectiveness of the Choosing Health programme as a means to promote weight loss and weight loss maintenance among overweight/obese adults.Methods and analysis The proposed study is a two-group randomised controlled trial with a nested interrupted time series (ITS) within-person design. Participants (n=285) will be randomly assigned to either the Choosing Health digital intervention or a control group. For intervention participants, ecological momentary assessment will be used to identify behavioural determinants for each individual in order to tailor evidence-based behaviour change techniques and intervention content.Control group participants will receive non-tailored weight loss advice via e-book and generic emails. The primary outcome is the mean difference in weight loss between groups at 6 months controlled for baseline. Secondary outcomes include blood pressure and percentage of body fat; self-reported measures of physical activity, sitting time, quality of life, cost and theory-derived correlates of weight loss. Secondary outcomes will be measured at baseline, 3, 6 and 12 months. The primary outcome for ITS will be daily weight loss plan adherence. Data will be analysed using regression and time series analyses.Ethics and dissemination Ethics approval was granted by Faculty of Psychology, SWPS University of Social Sciences and Humanities, Wroclaw, Poland, approval number 03/P/12/2019. The project results will be disseminated through structured strategy implemented in collaboration with the Ministry of Health.Trial registration details This trial was registered with www.clinicaltrials.gov; registration number NCT04291482.